Phenotypic study of Macrolide-Lincosamide-Streptogramin B Resistance in Staphylococcus aureus and their relationship with Methicillin-Resistant Staphylococcus aureus (MRSA) at Tertiary Care in Eastern Nepal - Singh, Ganesh Kumar; Chaudhari, Bigu Kumar; Parajuli, Kamal Prasad (Journal of Nobel Medical College, 2016)
Background Resistance to antimicrobial agents is prevalent among Staphylococci. This has led to wide uses of macrolide-lincosamide-streptogramin B (MLSB) antibiotics to Staphylococcus aureus (S. aureus) infections. MLSB though chemically distinct, have similar target site and mode of action. The multiple mechanisms are responsible for resistance to MLSB antibiotics which can lead to clinical failure. The aim of the study was to investigate the frequency of inducible and constitutive clindamycin resistance among clinical isolates of S. aureus and their relationship with Methicillin-resistant Staphylococcus aureus (MRSA). Material & Methods A total of 336 unique Staphylococcus aureus isolates from different clinical samples obtained from patients were studied. Antibiotic susceptibility test was performed by Kirby- Bauer disc diffusion method. “D test” was performed to detect inducible clindamycin resistance as per CLSI guidelines. MRSA was detected using Cefoxitin (30μg) and results were interpreted according to CLSI criteria. Results Inducible clindamycin resistance was seen in 45 (13.39%), constitutive clindamycin resistance was seen among 58 (17.26%) while MS phenotype was observed among 38(11.30%) of isolates. Inducible resistance as well as constitutive resistance was higher among MRSA as compared to MSSA (21.11%, 4.48% and 21.11%, 12.82%respectively). Conclusion The Successful use of clindamycin for the treatment of infection caused by S. aureus can be predicted based on the result of simple and inexpensive D test. Journal of Nobel Medical College Volume 5, Number 1, Issue 8, January-July 2016, 1-5